Request for MEP materials supply for prototype room of PT2 toilet on GF - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request for MEP materials supply for prototype room of PT2 toilet on GF of BRACU new campus building.